Evaluasi Penerapan Protokol Kesehatan Pencegahan Penyebaran COVID-19 dalam Pembelajaran Praktik di Laboratorium Program Studi Kebidanan Poso - Marlina Fitriya Lailatul K; K Khuzaifah (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
Laboratory is one of the important facilities and infrastructure in the learning process, especially Vocational Higher Education which has a larger practical curriculum than theory. The COVID-19 pandemic that is happening in the world makes learning in higher education implemented online. However, vocational colleges in the health sector find it difficult to carry out practical learning without meeting face to face. This study aims to determine the application of health protocols to prevent the spread of COVID-19 in practical learning at the Poso Midwifery Laboratory. This study uses a descriptive method with a qualitative design. The sampling technique was purposive sampling. Data were collected by filling out questionnaires and in-depth interviews with several samples. The results of this study indicate that the application of health protocols to prevent the spread of COVID-19 is quite good with details of the student aspects of 98.6%, laboratory staff aspects of 99.2%, lecturers' aspects of 100%, management aspects of 98.9%, and facility aspect of 96.4.%.